CRISPR/dCas-mediated counter-silencing: reprogramming dCas proteins into antagonists of xenogeneic silencers - Johanna Wiechert; Biel Badia Roigé; Doris Dohmen-Olma; Hindra; Xiafei Zhang; Roberto G. Stella; Marie A. Elliot; Julia Frunzke (mBio)
ABSTRACT Lsr2-like nucleoid-associated proteins function as xenogeneic silencers (XSs) inhibiting expression of horizontally acquired, adenine-thymine-rich DNA in actinobacteria. Interference by transcription factors can lead to counter-silencing of XS target promoters, but relief of this repression typically requires promoter engineering. In this study, we developed a novel clustered regularly interspaced short palindromic repeats (CRISPR)/dCas-mediated counter-silencing (CRISPRcosi) approach by using nuclease-deficient dCas enzymes to counteract the Lsr2-like XS protein CgpS in Corynebacterium glutamicum or Lsr2 in Streptomyces venezuelae. Systematic in vivo reporter studies with dCas9 and dCas12a and various guide RNAs revealed effective counter-silencing of different CgpS target promoters in response to guide RNA/dCas DNA binding, independent of promoter sequence modifications. The most prominent CRISPRcosi effect was observed when targeting the CgpS nucleation site, an effect that was also seen in S. venezuelae when targeting a known Lsr2 nucleation site within the chloramphenicol biosynthesis gene cluster. Analyzing the system in C. glutamicum strains lacking the XS protein CgpS revealed varying strengths of counteracting CRISPR interference effects based on the target position and strand. Genome-wide transcriptome profiling in single-guide RNA/dCas9 co-expressing C. glutamicum wild-type strains revealed high counter-silencing specificity with minimal off-target effects. Thus, CRISPRcosi provides a promising strategy for the precise upregulation of XS target genes with significant potential for studying gene networks as well as for developing applications in biotechnology and synthetic biology.IMPORTANCELsr2-like nucleoid-associated proteins act as xenogeneic silencers (XSs), repressing the expression of horizontally acquired, adenine-thymine-rich DNA in actinobacteria. The targets of Lsr2-like proteins are very diverse, including prophage elements, virulence gene clusters, and biosynthetic gene clusters. Consequently, the targeted activation of XS target genes is of interest for fundamental research and biotechnological applications. Traditional methods for counter-silencing typically require promoter modifications. In this study, we developed a novel clustered regularly interspaced short palindromic repeats (CRISPR)/dCas-mediated counter-silencing (CRISPRcosi) approach, utilizing nuclease-deficient dCas enzymes to counteract repression by Lsr2-like proteins in Corynebacterium glutamicum and Streptomyces venezuelae. The strongest effect was observed when targeting the Lsr2 nucleation site. Genome-wide transcriptome profiling revealed high specificity with minimal off-target effects. Overall, CRISPRcosi emerges as a powerful tool for the precise induction of genes silenced by xenogeneic silencers, offering new opportunities for exploring gene networks and advancing biotechnological applications.